2012
DOI: 10.1074/jbc.m111.319426
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Pro-apoptotic Protein Bim and Down-regulation of Anti-apoptotic Protein Mcl-1 Cooperatively Mediate Enhanced Tumor Cell Death Induced by the Combination of ERK Kinase (MEK) Inhibitor and Microtubule Inhibitor

Abstract: Background: MEK inhibitors enhance apoptosis induction by microtubule inhibitors. Results: MEK and microtubule inhibitors together induced up-regulation of Bim and down-regulation of Mcl-1 in association with prolongation of mitosis. Conclusion:The drug combination tips the balance between pro-and anti-apoptotic signaling toward induction of cell death. Significance: The combination of MEK inhibitors with agents that down-regulate or inactivate anti-apoptotic proteins is a promising anticancer strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
2
17
0
1
Order By: Relevance
“…These results implicate that increased proteasome activity in the absence of Msx was to counteract the burden of unfolded/misfolded proteins caused by enhanced translation and ER stress. This is consistent with increased incidence of pseudoimplantation sites with bortezomib (57). Indeed, we found increased population of Bippositive cells and higher Bip levels in bortezomib-treated Msx1/ Msx2 d/d uteri consistent with aggravated ER and proteotoxic stress (Fig.…”
Section: The Ubiquitin-proteasome System Is Enriched In Msx1/ Msx2 D/supporting
confidence: 75%
“…These results implicate that increased proteasome activity in the absence of Msx was to counteract the burden of unfolded/misfolded proteins caused by enhanced translation and ER stress. This is consistent with increased incidence of pseudoimplantation sites with bortezomib (57). Indeed, we found increased population of Bippositive cells and higher Bip levels in bortezomib-treated Msx1/ Msx2 d/d uteri consistent with aggravated ER and proteotoxic stress (Fig.…”
Section: The Ubiquitin-proteasome System Is Enriched In Msx1/ Msx2 D/supporting
confidence: 75%
“…Furthermore, Kawabata and colleagues have suggested, in a preclinical study, an interesting possibility that efficacy of the combination with microtubule inhibitors and MEK inhibitors is largely schedule dependent (44). The study demonstrated that when the microtubule inhibitor was administered first followed by a MEK inhibitor, cell death was observed, but not when the sequence was reversed (44). This observation may be related to the different phases of the cell cycle in which MEK inhibitors and chemotherapy act.…”
Section: Nsclc (Select-1) Has Been Initiated (Nct 01933932)mentioning
confidence: 85%
“…Microtubule inhibitors, such as taxanes or vinorelbine, can lead to activation of the RAS-ERK pathway, and combining MEK inhibitors with these agents suppressed RAS-mediated signaling and increased the efficacy of the drugs in treatment of cancer (49,50). Furthermore, Kawabata and colleagues have suggested, in a preclinical study, an interesting possibility that efficacy of the combination with microtubule inhibitors and MEK inhibitors is largely schedule dependent (44). The study demonstrated that when the microtubule inhibitor was administered first followed by a MEK inhibitor, cell death was observed, but not when the sequence was reversed (44).…”
Section: Nsclc (Select-1) Has Been Initiated (Nct 01933932)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, up-regulation of BIM may offer the greatest potential to improve therapeutic efficacy. However, the induction of BIM proteins by MEK/ERK inhibition (15,16) can result in BIM being bound and inhibited by anti-apoptotic BCL-2 and/or BCL-XL, which are frequently overexpressed in solid tumors (17). This antagonism may explain the modest apoptotic and largely cytostatic effect of MEK/ERK inhibitors in KRAS mutant tumor xenografts (18) as well as predominantly stable disease in patient studies (6,7).…”
mentioning
confidence: 99%